Early enteral feeding in patients with gastrointestinal surgery time to send the patient home early - Soni, Deepak Kumar; Sharma, Shrikant; Khan, Shehtaj (International Surgery Journal, 2022)
Background: There has been a trend among surgeons to delay enteral feeding following gastrointestinal surgery so that complications like anastomotic site leak and infection can be prevented and also to give time for operated site to heal. Newer studies suggest that early enteral feeding is useful in comparison to conventional method of feeding i.e. waiting for bowel function to return. This study was undertaken to evaluate the safety and tolerability of early enteral feeding after gastrointestinal surgeries in terms of postoperative complications and length of hospitalization. Methods: This study was prospective observational study with retrospective controls done over a period of 18 months at a tertiary care center in India. 35 patients were included in each group (case versus control). Early enteral feeding was defined as commencement of oral feed within 48 hours of surgery. The data was analyzed using statistical package of social science (SPSS Version 20; Chicago Inc., USA). Results: Both groups were found to be well matched in terms of age and sex distribution. The mean hospital stay for patients given early enteral feeding was significantly lower as compared to controls (10.26±3.09 versus 13.4±2.186). They had a complication rate of 11.4 % as compared to late enteral feeding group (25.7%). Conclusions: Early enteral feeding has been found beneficial in most of the studies worldwide. Hence, it is time to open our minds and embrace it to improve surgical outcome in gastrointestinal surgery practice.